Governança Corporativa no modelo da Organização Social de Saúde do Estado de São Paulo - Pereira, Rosania Nascimento (2014)
Part of the Reform Plan of the State's strategy was to transfer at the end of the 90s, to the non public sector producing services such as health, education and culture, seeking to promote greater efficiency and quality services. A key strategy was the creation of social organizations (OS). Since 1998, the State Health Department of São Paulo (SES) transferred the management of hospitals to these organizations through management contracts that discriminated objectives and targets to be achieved for the production of health services. Due to the fact that it was the management of public money, the corporate governance issue was relevant to public administration. The research evaluates the governance in the social organization of health SPDM - Association for the Development of Medicine as the criteria for accountability (account responsibility) and transparency through the analysis of existing, contracts and reports that regulate OSS legislation. The research results show that the criteria for accountability and transparency - important to ensure good governance in the public sector elements - according to the literature examined were not achieved considering that: the government of Sao Paulo is the main buyer, payer and performance controller of these organizations; in compliance with the time limits due to law enforcement for accountability; the quality of information of the S.E.S. to the departments of external control and the difficulty of access to information for stakeholders